Do remittances promote economic growth and reduce poverty? Evidence from Latin American countries - E. M. Ekanayake; Carlos Moslares (Economies, 2020)
In this study, we explore the hypotheses that (a) workers' remittances enhance economic growth in Latin American countries, and (b) workers' remittances help reduce poverty in Latin American countries. In recent decades, workers' remittances have become an important source of income for many developing countries and, as a global aggregate, workers' remittances are the largest source of foreign financing after foreign direct investment. This paper analyzes the effects of workers' remittances on economic growth and poverty in 21 Latin American countries. The study uses annual data covering all Latin American countries for the period 1980-2018. We employ panel least squares and panel fully-modified least squares (FMOLS) methods. In addition, we estimate the short-run and long-run effects of workers' remittances on economic growth and poverty on individual countries with the Autoregressive Distributed Lag (ARDL-ECM) approach to co-integration analysis. The results reveal that workers' remittances have a positive effect on long-run economic growth in the majority of the countries studied, but have mixed effects in the short-run. They also suggest that workers' remittances tend to lower poverty rates in Latin America.
Keywords: F24; F43; I30; O47; 330; economic growth; ARDL; FMOLS; Latin America; poverty; remittances